Structural Dynamics of the Activation of Elongation Factor 2 Kinase by Ca2 +-Calmodulin. Issue 17 (17th August 2018) - Will, Nathan; Lee, Kwangwoon; Hajredini, Fatlum; Giles, David H.; Abzalimov, Rinat R.; Clarkson, Michael; Dalby, Kevin N.; Ghose, Ranajeet
Abstract: Eukaryotic elongation factor 2 kinase (eEF-2K), the only known calmodulin (CaM)-activated α-kinase, phosphorylates eukaryotic elongation factor 2 (eEF-2) on a specific threonine (Thr-56) diminishing its affinity for the ribosome and reducing the rate of nascent chain elongation during translation. Despite its critical cellular role, the precise mechanisms underlying the CaM-mediated activation of eEF-2K remain poorly defined. Here, employing a minimal eEF-2K construct (TR) that exhibits activity comparable to the wild-type enzyme and is fully activated by CaM in vitro and in cells, and using a variety of complimentary biophysical techniques in combination with computational modeling, we provide a structural mechanism by which CaM activates eEF-2K. Native mass analysis reveals that CaM, with two bound Ca 2 + ions, forms a stoichiometric 1:1 complex with TR. Chemical crosslinking mass spectrometry and small-angle X-ray scattering measurements localize CaM near the N-lobe of the TR kinase domain and the spatially proximal C-terminal helical repeat. Hydrogen/deuterium exchange mass spectrometry and methyl NMR indicate that the conformational changes induced on TR by the engagement of CaM are not localized but are transmitted to remote regions that include the catalytic site and the functionally important phosphate binding pocket. The structural insights obtained from the present analyses, together with our previously published kinetics data, suggest that TR, and by inference, wild-type eEF-2K, upon engaging CaM undergoes a conformational transition resulting in a state that is primed to efficiently auto-phosphorylate on the primary activating T348 en route to full activation. Graphical abstract: Unlabelled Image Highlights: eEF-2K phosphorylates eEF-2 leading to a suppression of translational elongation. A minimal, fully functional construct, TR, of eEF-2K has been developed. The architecture of the complex between calmodulin and TR has been defined. Engagement of calmodulin leads to significant conformational changes in TR including at remote sites. This study provides insight into the calmodulin-mediated activation of eEF-2K.